Implementasi Manajemen Pendidikan Islam Berbasis Karakter: Strategi Pembangunan Karakter Siswa di Madrasah - Sujarwo, Agus (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
The purpose of this study is to investigate the management of Islamic education based on the character based on the context of the development of Madrasas students. The main purpose of this study is to identify the management strategy that can be implemented in Madrasus in creating character characters, thanks to Islamian educational approaches. This study uses a method of reviewing the literature and analyzing various relevant reading sources, such as books, magazines, articles, and previous studies related to Islam education and character training management. Research results indicate that natural -based educational management can be implemented using three major pillars. First, integration into the learning process of the character learning program. Second, the role of Maras leaders in the supply of samples and politics management that supports the formation of personality. Third, when creating an environment that supports the development of student characters, it is to strengthen the sluggishness and cooperation between families and communities. Some of the challenges faced are the lack of trained human resources in character education and the lack of synergy between schools, parents and society. In conclusion, character-based management of Islamic madrasah education is very important to create a generation that is not only academically intelligent but also possesses noble character. For this reason, more comprehensive policies and closer cooperation between schools, parents and society are needed to implement personality education